Submucosal Inferior Turbinoplasty Using a New Continuous Suction Irrigation Method - Kanaya, Takeo; Kohno, Naoyuki (Frontiers in Surgery, 2017)
Introduction: Numerous surgical techniques for inferior turbinate hypertrophy have been reported, each with advantages and disadvantages. Submucosal turbinoplasty with removal of the bony component of the inferior turbinate is an excellent procedure to expand the nasal cavity. However, this procedure requires a large incision to remove the inferior turbinate bone and is associated with hemorrhage, crust formation, and adhesion. A smaller incision would avoid such complications. We developed a continuous suction irrigation method that maintains a clear view of the limited surgical field of the inferior turbinate. Only a single small incision is needed to insert the rigid endoscope. The Surgeon can flush blood with continuous water flow and perform inferior turbinate surgery without difficulty. We performed this method in 39 cases from January, 2016 to January, 2017. This video article demonstrates our new submucosal inferior turbinoplasty technique. Methods: Submucosal turbinoplasty using a continuous suction irrigation method was performed under general anesthesia. An irrigation-suction straw sheath system was used to create an underwater surgical field. Results: The inferior turbinate bone was removed safely with no severe complications. An expanded common nasal cavity was confirmed postoperatively on computed tomographic images. Conclusions: We resected the inferior turbinate bone safely using a continuous suction irrigation method without difficulty or complications. We believe that this method may become one of the best surgical options for inferior turbinate hypertrophy.